Environmental flow provision: Implications for agricultural water and land-use at the global scale. (January 2015) - Bonsch, Markus; Popp, Alexander; Biewald, Anne; Rolinski, Susanne; Schmitz, Christoph; Weindl, Isabelle; Stevanovic, Miodrag; Högner, Kathrin; Heinke, Jens; Ostberg, Sebastian; Dietrich, Jan Philipp; Bodirsky, Benjamin; et al.
Highlights: Global assessment of land-use reactions to environmental flow protection. Environmental flow protection can be achieved with moderate land-use implications. Forest loss stays below 1% of current global forest area. Distribution of local impacts highlights the importance of non-local drivers. Abstract: Human activity has led to freshwater ecosystem degradation in the past and is likely to continue doing so if no appropriate protection mechanisms are implemented. One potential protection measure is the reallocation of water from human use to environmental purposes – also called environmental flows. Such reallocation may decrease the availability of irrigation water with possible adverse effects on agricultural production. In this analysis, we provide an initial quantitative estimate of how the allocation of annual volumes of water for environmental flow protection (EFP) might influence the food production system on a global scale. The application of a spatially explicit global land and water-use allocation model (MAgPIE) allows us to explore the effect of EFP on agricultural water withdrawals. We will also examine associated reactions in terms of land-use changes and agricultural intensification. Our results suggest that the implications of conserving annual volumes of water for EFP on the land-use system are moderate on an aggregate global level. Cropland expansion into unmanaged land arising from increased food demand up to 2045 is higher by a factor 5–9 than cropland expansion induced by EFP. Global forest losses associated with EFP remain below 1% of current forest area. Production reallocation and associated land-use change hotspots suggest that local effects are of more concern than aggregate cropland expansion and deforestation.